Contribution of Crystal Lattice Energy on the Dissolution Behavior of Eutectic Solid Dispersions - Chaturvedi, Kaushalendra (ACS Omega, 2020)
[Image: see text] In the literature, it is reported that eutectics lead to the enhanced dissolution of a poorly soluble compound. However, the solubility theory suggests that since crystal structures of two components are unchanged that all else being equal, the dissolution rates of a fused mixture (FM) should be the same as a physical mixture (PM). The influence of crystal lattice energy on dissolution profiles was investigated using the PM and FM. Experimental phase diagrams constructed using differential scanning calorimetry data were compared with those theoretically derived. Deviation of the experimental phase diagram curves from the theoretical model indicates the nonideal behavior of both systems (ibuprofen/poly(ethylene glycol)-6000 and acetaminophen/caffeine). Both the binary systems showed an increase in the dissolution rate of the PM and FM. However, the dissolution from the PM was comparable with the FM’s dissolution profile. The theoretical solubility calculations using the modified solubility equation showed that the use of the eutectic temperature instead of the drug’s melting point should give a 3–4-fold increase in drug solubility. However, the correlation between dissolution and solubility calculation showed that the FM did not improve the dissolution when compared with the respective PM’s dissolution profile. The proposed explanation is that the unchanged crystal lattice energy in eutectics still limits the solubility and therefore the dissolution rate.